1980
DOI: 10.1128/jb.141.3.1450-1453.1980
|View full text |Cite
|
Sign up to set email alerts
|

Is cyclic guanosine 3',5'-monophosphate a cell cycle regulator?

Abstract: Transient increases in the intracellular level of cyclic guanosine 3',5'-monophosphate have been observed at a periodicity of one generation time in two spoT strains of Escherichia coli and in Bacillus lichenifornis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Bernlohr et al (22), using a complex enzyme cycling assay, found cGMP to be present in concentrations as high as 30 nM in E. coli. With a more conventional radioimmune assay, steady-state intracellular concentrations of cGMP of 0.5 to 3 nM were found (40). In other experiments, these authors obtained synchronous division by starving cells for various nutrients.…”
Section: A C 260bmentioning
confidence: 96%
See 1 more Smart Citation
“…Bernlohr et al (22), using a complex enzyme cycling assay, found cGMP to be present in concentrations as high as 30 nM in E. coli. With a more conventional radioimmune assay, steady-state intracellular concentrations of cGMP of 0.5 to 3 nM were found (40). In other experiments, these authors obtained synchronous division by starving cells for various nutrients.…”
Section: A C 260bmentioning
confidence: 96%
“…Cook et al (40) observed a sharp increase in cGMP levels in B. licheniformis undergoing synchronous division with a periodicity equivalent to one generation. They proposed that cGMP could be involved in some aspect of regulation of cellular division.…”
Section: Cyclic Nucleotides In Dimorphicmentioning
confidence: 99%
“…For example, a sudden change in the cytoplasmic calcium concentration has been proposed as a signal for a number of cell cycle events (76,123). Cyclic nucleotides have also been suggested as being involved in cell cycle regulation (25). The evidence for division cycle variations in the concentrations or amounts of various cytoplasmic substances have been considered.…”
Section: Regulation Of Surface Synthesis By Cytoplasmic Signalsmentioning
confidence: 99%
“…A class of mutants has been described recently which contains a cya mutation and yet expresses many, if not all, operons requiring the cAMP-CRP complex for positive control (1,5,6,21,26). Genetic analysis showed that these cya suppressor strains contain a second-site mutation that lies in the crp gene (1,5,6,21,26). Takebe et al (26) provided biochemical evidence that the cya suppressor mutation resulted in the production of an altered CRP.…”
mentioning
confidence: 99%